THE EFFECT OF BUSINESS STRATEGIES AND ENVIRONMENTAL UNCERTAINTY ON TAX AVOIDANCE IN MANUFACTURING COMPANIES IN INDONESIA - Farhan Satria Akbar; Meiryani Meiryani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the Effect of Business Strategy and Environmental Uncertainty on Tax Avoidance in companies listed on the Indonesia Stock Exchange for the period 2018-2020. The dependent variable used is Tax Avoidance, the independent variable used is Business Strategy and Environmental Uncertainty and includes five types of control variables consisting of leverage, property, plant and equipment, inventory intensity, company size and return on assets. The statistical analysis tool used in this study is SPSS 25. The results of this study indicate that prospector and defender business strategies have a significant effect on tax avoidance, while environmental uncertainty has no effect on tax avoidance.